Analisis Perbandingan Model Altman, Springate dan Grover dalam Memprediksi Kebangkrutan pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Oviana Intan Ayu; Agustina Widodo (Universitas Sains dan Teknologi Komputer, 2025)
Bankruptcy is a condition where a business cannot operate effectively due to severe financial difficulties it is currently experiencing. This research purposes to analyze the ratio of the Altman, Springate, and Grover models in analyzing bankruptcy in food and beverage corporations listed on the IDX with reference to signaling theory. The data analysis approach used are One Way Anova test and accuracy level test. Using 20 company samples with purposive sampling method. The final proceeds of the research explain that there are significant differences between the Altman and Springate models, significant differences between the Altman and Grover models, and no significant differences between the Springate and Grover models in predicting bankruptcy in food and beverage companies for the period 2019-2023. The very accurate prediction model was achieved by the Grover model.